Collaborative responses to cyberbullying: preventing and responding to cyberbullying through nodes and clusters. (2nd October 2016) - Broll, Ryan
Abstract : The distributed nature of cyberspace requires that security issues be addressed within plural policing environments in which public and private actors work together to form a security quilt. Cyberbullying is increasingly recognised as a serious social concern and a legitimate security threat that affects a large number of young people in cyberspace. Drawing on nodal governance theory, this article uses data from in-depth qualitative interviews with 34 members of the parent, educational system and law enforcement nodal clusters to explore adults' responses to cyberbullying. In particular, I examine the types of capital possessed by each cluster, their position within the cyberbullying security network, how they achieve security and limitations experienced by each cluster. The parent cluster was identified as central to the security network, whereas the educational system occupies a secondary position and the law enforcement cluster serves primarily as a knowledge broker. Each cluster is limited by a lack of familiarity and a comfort with cyberspace and electronic communications. An examination of internodal relations revealed several gaps in the security network and a number of structural and cultural variables that limit the network's security potential.